PENANAMAN DAN PENGOLAHAN TOGA (BUNGA ROSELA, DAUN INGSULIN, DAUN AFRIKA, DAUN BINAHONG, MAHKOTA DEWA, DAUN DEWA, BUNGA MENTEGA) - Budiono, Sunu Catur (LPPM Universitas PGRI Adi Buana Surabaya, 2017)
Related to the health of rural communities a wide range of medicines here TOGA program implemented because the plant needed an alternative treatment that can be done independently to create an environment and a healthy society. TOGA is the cultivation of plants that have medicinal properties housing. Parks family medicine is essentially a piece of land either in the yard, garden, or fields used to cultivate plants that have medicinal properties in order to meet family needs will be drugs. In addition to planting program will be completed subsequent processing of TOGA investment process with a wide range of processing results. Hopefully the use of TOGA able to create a society that is able to maintain good health with traditionally.